A network model of the molecular organization of chromatin in Drosophila - van Bemmel, Joke G; Filion, Guillaume J; Rosado, Arantxa; Talhout, Wendy; de Haas, Marcel; van Welsem, Tibor; van Leeuwen, Fred; van Steensel, Bas (Molecular cell, 2013)
Chromatin governs gene regulation and genome maintenance, yet a substantial fraction of the chromatin proteome is still unexplored. Moreover, a global model of the chromatin protein network is lacking. By screening >100 candidates we identify 42 Drosophila proteins that were not previously associated with chromatin, which all display specific genomic binding patterns. Bayesian network modeling of the binding profiles of these and 70 known chromatin components yields a detailed blueprint of the in vivo chromatin protein network. We demonstrate functional compartmentalization of this network, and predict functions for most of the previously unknown chromatin proteins, including roles in DNA replication and repair, and gene activation and repression.